Time-resolved Kα spectroscopy measurements of hot-electron equilibration dynamics in thin-foil solid targets: collisional and collective effects. (25th September 2015) - Nilson, P M; Solodov, A A; Davies, J R; Theobald, W; Mileham, C; Stoeckl, C; Begishev, I A; Zuegel, J D; Froula, D H; Betti, R; Meyerhofer, D D
Abstract: Time-resolved K α spectroscopy measurements from high-intensity laser interactions with thin-foil solid targets are reviewed. Thin Cu foils were irradiated with 1−10 J, 1 ps pulses at focused intensities from 10 18 to 10 19 W cm −2 . The experimental data show K α -emission pulse widths from 3 to 6 ps, increasing with laser intensity. The time-resolved K α -emission data are compared to a hot-electron transport and K α -production model that includes collisional electron–energy coupling, resistive heating, and electromagnetic field effects. The experimental data show good agreement with the model when a reduced ponderomotive scaling is used to describe the initial mean hot-electron energy over the relevant intensity range.